Dot1-dependent histone H3K79 methylation promotes the formation of meiotic double-strand breaks in the absence of histone H3K4 methylation in budding yeast. - Mohammad Bani Ismail; Miki Shinohara; Akira Shinohara (PLoS ONE)
Epigenetic marks such as histone modifications play roles in various chromosome dynamics in mitosis and meiosis. Methylation of histones H3 at positions K4 and K79 is involved in the initiation of recombination and the recombination checkpoint, respectively, during meiosis in the budding yeast. Set1 promotes H3K4 methylation while Dot1 promotes H3K79 methylation. In this study, we carried out detailed analyses of meiosis in mutants of the SET1 and DOT1 genes as well as methylation-defective mutants of histone H3. We confirmed the role of Set1-dependent H3K4 methylation in the formation of double-strand breaks (DSBs) in meiosis for the initiation of meiotic recombination, and we showed the involvement of Dot1 (H3K79 methylation) in DSB formation in the absence of Set1-dependent H3K4 methylation. In addition, we showed that the histone H3K4 methylation-defective mutants are defective in SC elongation, although they seem to have moderate reduction of DSBs. This suggests that high levels of DSBs mediated by histone H3K4 methylation promote SC elongation.